2018
DOI: 10.1038/s41598-018-21521-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-level Gestational Lead Exposure Alters Dendritic Spine Plasticity in the Hippocampus and Reduces Learning and Memory in Rats

Abstract: Lead (Pb) is known to impair children’s cognitive function. It has been previously shown that developmental Pb exposure alters dendritic spine formation in hippocampal pyramidal neurons. However, the underlying mechanism has not yet been defined. In this study, a low-level gestational Pb exposure (GLE) rat model was employed to investigate the impact of Pb on the spine density of the hippocampal pyramidal neurons and its regulatory mechanism. Pb exposure resulted in impaired performance of the rats in the Morr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 57 publications
1
26
0
1
Order By: Relevance
“…Similarly, animals exposed to lead either prenatally or postnatally develop memory impairment and cognitive decline later in life [241,242] . Recently, it has been reported that low-level gestational lead exposure results in dendritic spine alterations in the hippocampus by down-regulating neuroligin-1 protein levels, which in turn results in learning and memory impairment [243] . Given that the effects of early life exposure to lead can persist in adulthood, it is possible that this contributes to the development of AD.…”
Section: The Non-essential Metals Lead (Pb)mentioning
confidence: 99%
“…Similarly, animals exposed to lead either prenatally or postnatally develop memory impairment and cognitive decline later in life [241,242] . Recently, it has been reported that low-level gestational lead exposure results in dendritic spine alterations in the hippocampus by down-regulating neuroligin-1 protein levels, which in turn results in learning and memory impairment [243] . Given that the effects of early life exposure to lead can persist in adulthood, it is possible that this contributes to the development of AD.…”
Section: The Non-essential Metals Lead (Pb)mentioning
confidence: 99%
“…The Golgi method of staining has long proven to be a reliable method for assessing dendrite and dendritic spine dynamics due to various conditions, because of its resistance to fading or photobleaching over time. (29,30) We adapted a staining protocol and used the reagents contained in the superGolgi kit (Bioenno Tech). (31) Right hemispheres were immediately impregnated in a potassium dichromate solution for two weeks (n = 5).…”
Section: Golgi Stainingmentioning
confidence: 99%
“…Synaptic plasticity in the hippocampus is essential to emotional and memory processes and is susceptible to environmental toxicants (Zhao et al, ; Vasilescu et al, ). Synaptic plasticity includes changes in the efficacy of synaptic transmission at preexisting synapses and structural plasticity—a term refers to structural changes through formation, modification, and elimination of existing synapses (Morris, Clark, Zinn, & Vissel, ).…”
Section: Introductionmentioning
confidence: 99%